Literature review: Potensi tepung kulit pisang kepok (Musa paradisiaca L.) sebagai pencegahan stunting di Indonesia - Muthmainnah, Aisya Kayla (Maliki Interdisciplinary Journal, 2024)
Stunting is a public health problem where height does not match age. One way to prevent stunting is to meet the nutritional needs of pregnant women and babies. The aim of this research is to determine the potential of Kepok Banana Peel Flour (Musa paradisiaca L.) as a prevention of stunting. The method used in this research is a literature review from various journal sources. Kepok banana peel (Musa paradisiaca L.) has a lot of nutritional content, including carbohydrates, fat, protein, dietary fiber, calcium, phosphorus, iron, vitamin B, vitamin C, and pectin, but it has a tart or bitter taste, so it must be processed into flour. so that the tannin content decreases. Kepok banana peels that have been processed into flour tend to have a higher nutritional content than those that have not undergone processing.